A study of VP shunt in management of hydrocephalus - Pal, Sudhir Singh; Dubey, Saurabh (International Surgery Journal, 2017)
Background: Hydrocephalus a neurological disorder common in both children and adults. VP shunt placement is considered the mainstay of management. The aim was to study complications of VP Shunt and factors influencing shunt malfunction and prognosis. Methods: This study was conducted in the Department of Surgery, Gandhi Medical College Bhopal, Madhya Pradesh, India between January 2013 to August 2016 and included all patients of hydrocephalus who underwent VP shunt surgery. We performed a retrospective and prospective data review which was subjected to statistical analysis, frequency determination, determination of mean and standard deviation, Pearson’s Chi-square test for studying associations between variables. Results: A total of 198 patients were studied. The predominant etiologies being congenital hydrocephalus, aqueduct stenosis, spina bifida/MMC, intracranial space occupying lesions and tuberculous meningitis. The incidence of overall shunt complications was 28.8%, incidence of shunt revision was 21.2%, shunt blockade 7.6%), shunt migration 5.05%, shunt infection 4.5%, and shunt malfunction due to other causes 8.6%. The mortality rate was 20.2%. Factors associated with increased shunt complications included infective etiology of the hydrocephalus and CSF culture positivity in preoperative period. Conclusions: Infective and traumatic causes of hydrocephalus are more likely to be associated with complications like infection and obstruction. Shunt migration is seen in paediatric patients.